Self-Reported and Objectively Measured Physical Activity of Males from 50 to 69 Years Old - Milena Mitrovic (Journal of Anthropology of Sport and Physical Education)
Considering the impact of physical activities on the health, physical development and psychological aspects of the individual, it is necessary to monitor their application in all life periods, even in the older age. On the sample of 100 male examinees from 50 to 69 years of age from Niksic, using the survey IPAQ questionnaire, we tried to determine the level of physical activity in the work, transportation, jobs in the yard and at home and in their spare time. The results showed that respondents spend the most time in performing physical activity at work. Respondents spend the least amount of time in performing physical activities in transport. Also, respondents from 50 to 60 years are significantly more physically active than respondents from 60 to 69 years of age.